2013
DOI: 10.1109/lpt.2013.2283732
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Temperature Measurements With Liquid-Core Microbubble Resonators

Abstract: The thermal shifting of whispering gallery modes (WGMs) in a microbubble resonator is investigated. The thermal shift rate is determined for different modes when the core of the microbubble is filled with air, water and ethanol. Sensitivities as high as 100 GHz/K (0.2 nm/K at wavelength of 775 nm) are observed when the microbubble core is filled with ethanol. This is the largest thermal shift rate reported for a WGM resonator. We also show that thermal behavior of the WGMs in a thin-shelled, air-filled microbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…filled the microbubbles with water, ethanol, and air to study the thermal displacement rates under different modes. The results showed that when filling ethanol, the highest sensitivity is 100 GHz K −1 , which was the maximum displacement rate of the current resonator . Conventional microbubble resonators were single‐input and single‐output.…”
Section: Structure and Application Of Wgmrsmentioning
confidence: 95%
“…filled the microbubbles with water, ethanol, and air to study the thermal displacement rates under different modes. The results showed that when filling ethanol, the highest sensitivity is 100 GHz K −1 , which was the maximum displacement rate of the current resonator . Conventional microbubble resonators were single‐input and single‐output.…”
Section: Structure and Application Of Wgmrsmentioning
confidence: 95%
“…The sensitivity can be improved by using shorter-wavelength light (780 nm), with a maximum resolution of 0.17 mbar [30]. Similarly, changes in temperature will also give rise to a shift in the resonances, which can be used as a thermometer, with a demonstrated sensitivity of up to 0.20 nm/K in an ethanol-filled microbubble [43]. …”
Section: Applications To Sensingmentioning
confidence: 99%
“…If the MBR's shell is thin enough, most of the optical fields can penetrate into the core, which maximizes the interaction with the medium inside. The outstanding advantage makes MBRs as one of promising optofluidic platforms for ultra-sensitive chemical and bio-sensing [16][17][18]. However, the application of MBRs in optical trapping or manipulation has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%